The impact of Helicobacter pylori eradication with vonoprazan-amoxicillin dual therapy combined with probiotics on oral microbiota: a randomized double-blind placebo-controlled trial - Peng, Ruolin; Zhang, Zhenyu; Qu, Yi; Chen, Weiwei (Frontiers in Microbiology, 2023)
Background: Helicobacter pylori (H. pylori) infection and eradication have been reported to cause dysbiosis of the oral microbiota. Probiotics are increasingly being used to maintain the balance of the oral microbiota. We aimed to investigate the effects of H. pylori infection, H. pylori eradication with vonoprazan-amoxicillin dual therapy, and probiotics supplementation on the oral microbiota.Methods: H. pylori positive patients were randomly assigned to a vonoprazan-amoxicillin regimen plus probiotics (BtT group) or the placebo (PT group) for 14 days. H. pylori negative pupulation served as normal controls. Tongue coating samples were collected from 60 H. pylori positive patients at three time points (before H. pylori eradication, after H. pylori eradication, and at confirmation of H. pylori infection cure) and 20 H. pylori negative subjects. 16S rRNA gene sequencing was used to analyze the oral microbiota.Results: H. pylori was detected in the oral cavity in positive (34/60), negative (7/20), and eradicated (1/60) subjects using high-throughput sequencing. Compared with normal controls, H. pylori positive patients exhibited higher richness (P = 0.012) and comparable diversity (P = 0.075) of oral microbiota. Beta diversity and KEGG analysis showed oral flora composition and function differences in H. pylori positive and negative subjects. Alpha diversity dramatically decreased after H. pylori eradication and modestly increased with confirmation of H. pylori eradication. Beta diversity and LEfSe analysis revealed distinct structures, and KEGG analysis showed distinct signaling pathways of tongue coating flora at three time points. There was a significant reduction of Firmicutes and Lactobacillus after H. pylori erdication. The PT group and BtT group had identical compositional and functional differences of oral microbiota at three time points.No substantial link existed between oral and stomach H. pylori, while removing gastric H. pylori helped eliminate oral H. pylori. H. pylori infection and vonoprazan-amoxicillin dual therapy affected oral microbiota diversity, structure, and function. H. pylori eradication demonstrated a suppressive impact on the proliferation of oral pathogens, specifically Firmicutes and Lactobacillus.